2011
DOI: 10.1371/journal.pone.0020661
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality Associated with Influenza Epidemics in Portugal, 1980 to 2004

Abstract: BackgroundInfluenza epidemics have a substantial impact on human health, by increasing the mortality from pneumonia and influenza, respiratory and circulatory diseases, and all causes. This paper provides estimates of excess mortality rates associated with influenza virus circulation for 7 causes of death and 8 age groups in Portugal during the period of 1980–2004.Methodology/Principal FindingsWe compiled monthly mortality time series data by age for all-cause mortality, cerebrovascular diseases, ischemic hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
3
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 35 publications
5
59
3
10
Order By: Relevance
“…We identified a greater impact of influenza A(H3N2) compared to influenza A(H1N1) and influenza B (Table 2, Table 3), which is similar to most other locations 3, 4, 6, 17, 19, 20. However, this observation is somewhat different to a previous study that estimated influenza B had a greater impact than influenza A(H3N2) in China, in the years 2003‐08 2.…”
Section: Discussionsupporting
confidence: 57%
“…We identified a greater impact of influenza A(H3N2) compared to influenza A(H1N1) and influenza B (Table 2, Table 3), which is similar to most other locations 3, 4, 6, 17, 19, 20. However, this observation is somewhat different to a previous study that estimated influenza B had a greater impact than influenza A(H3N2) in China, in the years 2003‐08 2.…”
Section: Discussionsupporting
confidence: 57%
“…1,3,4 In particular, older adults are considered to be at a higher risk for influenza-associated excess of mortality. 5,6 Influenza vaccination is still the most effective way to prevent the disease and reduce the mortality rate among elderly individuals, albeit its efficacy in this age group is modest. 1 Antunes et al 7 observed a reduction of 26% in the overall mortality due to influenza and pneumonia after the introduction of annual mass vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…En los años 2006, 2008 y 2010 no se produjo un exceso de mortalidad, años en los que se observó la circulación de virus influenza B y subtipo de influenza A (H1N1), que se conoce tienen baja severidad evidenciada por varios autores 14,[32][33][34][35][36][37][38][39][40] . Esto podría deberse a que en el caso de cepas A (H1N1) han circulado desde 1918, con un intervalo entre 1957 y 1977, y se ha ido adaptando a la población humana y viceversa 38 .…”
Section: Artículo Originalunclassified
“…Como consecuencia de la variabilidad de modelos aplicados a los datos de mortalidad utilizados en otros países, la comparación de los valores resulta muy compleja; sin embargo, se encuentran dentro del mismo rango 2,40 .…”
Section: Artículo Originalunclassified
See 1 more Smart Citation